Postgraduate student's perceptions on academic use of facebook - Bong, Charles Chee How (Universiti Malaysia Sarawak (UNIMAS), 2014)
The purpose of this study was to investigate the perceptions of Malaysian postgraduate students' in the Faculty of Cognitive Sciences and Human Development, Univer~iti Malaysia Sarawak (UNIMAS) of the academic use of Facebook (FB). This study examined the postgraduate students' current engagement with FB, perceptions of the use of FB for academic purposes, differences between male and female postgraduate students on their engagement in using FB and perceptions on the use of FB for academic purposes, and relationships between engagement in using FB and perceptions of using FB for academic purposes with FB use experiency This study used a cross-sectional survey. A total of 50 usable survey questionnaires were returned out of 55 '1uestionnaires distributed to all the Master of Science (Learning Sciences) postgraduate students in the Faculty of Cognitive Sciences and Human Development, UNIMAS. The findings of the study indicated several positive results. For example, postgraduate students perceived using FB for academic purposes was beneficial to them in formal and informal learning. They had been using FB more than 2 years and logged into FB more than 30 minutes daily. Furthermore, most ofthe participants kept in touch with their friends using FB and they felt that FB was convenient for them. They also used FB to interact with their classmates and they felt that FB was beneficial to students in enhancing their use of English Language at the university. There were no significant differences between male and female postgraduate students' engagement in FB and their perceptions of the use of FB for academic purposes. In addition, there were no significant relationships between engagement with FB and perceptions of using FB for academic purposes with FB use experience.